2011
DOI: 10.1002/jcu.20716
|View full text |Cite
|
Sign up to set email alerts
|

Right thoracic ectopic kidney in a child with breathing difficulties—Sonographic diagnosis

Abstract: Congenital intrathoracic ectopic kidney is a rare congenital abnormality that is usually found as an incidental lesion on chest radiographs. We report the case of a 6-month-old male with a 1-day history of breathing difficulties whose chest radiograph revealed a soft tissue right basilar mass. Further investigation utilizing ultrasound revealed a thoracic kidney. This case demonstrates the importance of sonography as a diagnostic tool in identifying thoracic kidneys in the pediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…They reach theirs adult location by the eighth week of gestation. At approximately the same gestational age, the pleuriperitoneal membrane forms the diaphragm leaflets [9,13]. Some have postulated that delayed closure of the pleuriperitoneal membrane permits excessive cranial migration of the kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reach theirs adult location by the eighth week of gestation. At approximately the same gestational age, the pleuriperitoneal membrane forms the diaphragm leaflets [9,13]. Some have postulated that delayed closure of the pleuriperitoneal membrane permits excessive cranial migration of the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical prevalence is much lower with only 13 pediatric cases reported over the last 25 years [2][3][4][5][6][7][8][9]. The pertinent literature is limited to case reports or very small case series.…”
mentioning
confidence: 96%
“…The location and anatomy of renal vessels in children with CIK reported in the pediatric literature were normal, except for one case [7][8][9]12]. Maduekwe et al [12] reported that the renal vessels in their cases were at higher than expected locations based on sonographic evaluation.…”
Section: Discussionmentioning
confidence: 95%
“…Maduekwe et al [12] reported that the renal vessels in their cases were at higher than expected locations based on sonographic evaluation. Our case had an absent IVC from the hepatic level, renal veins which formed a common vascular structure for draining to an enlarged azygos vein and bilateral accessory renal arteries.…”
Section: Discussionmentioning
confidence: 96%
“…Finalmente, la angiorresonancia magnética suele utilizarse para evaluar el origen y las características de la vasculatura renal. 4,5 El riñón ectópico intratorácico es casi siempre asintomático y funciona normalmente, por lo que su curso es benigno; sin embargo, puede producir dificultad respiratoria en el período neonatal o dolor debido a litiasis o infección urinaria.…”
Section: Comentario Riñón Ectópico Intratorácicounclassified